IMPACT OF GLOBAL WARMING ON MONSOON VARIABILITY IN PAKISTAN - A. Ghaffar; M. Javid (Journal of Animal and Plant Sciences, 2011)
This study is based on fifty years (1951-2000) data of temperature and rainfall from six different stations of Pakistan. The selection of the stations is based on hilly areas that are totally dependant on rains. This study is divided into three parts Pre-Monsoon (April- May), Summer Monsoon (June- August) and Post Monsoon (September- October). Variation trends are analyzed based on the processed data that temperature is increasing during Pre and Post Monsoon while rainfall has over all decreasing trend during the study period. Pakistan needs better prediction of Monsoon, accurate calculation of water storage and losses, particularly for the agriculture use.
Keywords: Temperature; rainfall; Monsoon variability; prediction; Pakistan